# Difference between revisions of "MonadPlus reform proposal"

From HaskellWiki

Line 17: | Line 17: | ||

satisfying '''Monoid''' and '''Left Distribution''': | satisfying '''Monoid''' and '''Left Distribution''': | ||

− | mplus mzero | + | mplus mzero b = b |

mplus a mzero = a | mplus a mzero = a | ||

mplus (mplus a b) c = mplus a (mplus b c) | mplus (mplus a b) c = mplus a (mplus b c) | ||

Line 28: | Line 28: | ||

satisfying '''Monoid''' and '''Left Catch''': | satisfying '''Monoid''' and '''Left Catch''': | ||

− | morelse mzero | + | morelse mzero b = b |

morelse a mzero = a | morelse a mzero = a | ||

morelse (morelse a b) c = morelse a (morelse b c) | morelse (morelse a b) c = morelse a (morelse b c) | ||

morelse (return a) b = return a | morelse (return a) b = return a | ||

+ | |||

+ | == Instances of both == | ||

+ | |||

+ | Some types could be made instances of both. For instance: | ||

+ | |||

+ | instance MonadOr [] where | ||

+ | morelse [] b = b | ||

+ | morelse a b = a |

## Revision as of 23:35, 15 January 2006

The MonadPlus class is ambiguous: while all instances satisfy **Monoid** and **Left Zero**, some such as `[]` satisfy **Left Distribution**, while others such as `Maybe` and `IO` satisfy **Left Catch**.

It is proposed that MonadPlus be split like this:

### MonadZero

class Monad m => MonadZero m where mzero :: m a

satisfying **Left Zero**:

mzero >>= k = mzero

### MonadPlus

class MonadZero m => MonadPlus m where mplus :: m a -> m a -> m a

satisfying **Monoid** and **Left Distribution**:

mplus mzero b = b mplus a mzero = a mplus (mplus a b) c = mplus a (mplus b c) mplus a b >>= k = mplus (a >>= k) (b >>= k)

### MonadOr

class MonadZero m => MonadOr m where morelse :: m a -> m a -> m a

satisfying **Monoid** and **Left Catch**:

morelse mzero b = b morelse a mzero = a morelse (morelse a b) c = morelse a (morelse b c) morelse (return a) b = return a

## Instances of both

Some types could be made instances of both. For instance:

instance MonadOr [] where morelse [] b = b morelse a b = a